The psychology of Mona Lisa’s smile - Alessandro Soranzo (Scientific Reports, 2024)
Abstract Mona Lisa’s ambiguous expression, oscillating between melancholy and contentment, has captivated viewers for centuries, prompting diverse explanations. This article proposes a novel interpretation grounded in the psychological theory of perceptual organisation. Central to the investigation is the “Ambiguity-Nuance”, a subtly shaded, blended region framing the upper part of the lips, hypothesised to influence perceived expression due to perceptual organization. Through carefully crafted artwork and systematic manipulations of Mona Lisa reproductions, experiments reveal how alterations in the perceptual relationships of the Ambiguity-Nuance yield significant shifts in perceived expression, explaining why Mona Lisa’s appearance changes and under which conditions she looks content versus melancholic based on perceptual organization. These findings underscore the pivotal role of psychological principles in shaping ambiguous expressions in the Mona Lisa, and extend to other Leonardo’s portraits, namely La Bella Principessa and Scapigliata. This study sheds light on the intersection of psychology and art, offering new perspectives on timeless masterpieces.